Dual-band absorber using low-profile multi-mode resonant units for controllable bandwidths. (29th December 2022) - Huang, Shengxiang; Wu, Yueyang; Deng, Lianwen; Qiu, Lei-Lei
Abstract: A dual-band quasi-single-layer absorber based on multimode resonance is proposed. Different from the traditional multi-substrate or multi-resonator composite structure, by virtue of stub- and slot-loaded technologies, only one single-substrate printed resonator is utilized to achieve multi-mode resonant characteristics for two absorption bands. The bandwidth of the two absorption bands can be adjusted by structural parameters. Through the detailed analysis of the surface current distribution in different modes, the generation principle of the multi-mode dual-band characteristic is revealed. Finally, the dual-band absorber is fabricated and measured, achieving dual-band absorptions in the frequency range of 7.64–10.8 GHz and 15.04–17.32 GHz with fractional bandwidth of 34.3% and 14.1%, respectively. The advantages of low-profile simple structure and controlled dual bandwidth make it very suitable for radar detection and stealth fields.